Hydraulic-Thermal Evaluation and Maintenance Prioritization for a District Geothermal Network in Berkeley, California - Shofi Latifah Nuha Anfaresi; Yulia Nugroho; Nanthaya Verweij (Departemen Teknik Sipil dan Lingkungan IPB, 2026)
District geothermal systems require reliable and efficient pressurized circulation and limited thermal dissipation in buried piping, yet design studies often report hydraulic or thermal behavior separately and rarely translate results into maintenance priorities. This study develops a one-way hydraulic-thermal screening workflow aiming to enhance the geothermal energy sustainability by designing a cyber-physical systems baseline. In the district closed-loop geothermal network, EPANET was used to model the full pressurized hydraulics system, while the heat-transfer calculation was evaluated separately from heat loss and heat exchange, coupled with hydraulic values. The operating cases used in the system is a 42-node, 40-pipe network with three 350 HP pumps, and an elevation range of 70-116 m. Outputs from EPANET, including link flow, velocity and head values were then exported to a separate steady heat loss calculation based on radial heat transfer under a uniform supply-return screening scenario. The methodological novelty in this study is the explicit combination of EPANET hydraulics with pipe-level heat-loss screening to investigate maintenance-critical pipes in a closed-loop geothermal network, rather than only reporting system operating metrics. The simulations indicate daily pumping energy of 17,896.8 kWh under the assumed work cycle with hydraulically acceptable velocities of approximately 3-5 fps. The average heat loss in the system is at around 0.0357 kWh/day with almost half of the system’s pipes are pipes with heat loss values above average and considered critical. These pipes are the overheat pipes with wider diameter and mostly considered as main transmission pipes in the geothermal system loop. The use of enhanced insulated pipes and automated sensing devices installations in these critical pipes in the geothermal construction plan would create a significant contribution towards the operation and maintenance work and overall system’s sustainability. This result is interpreted as a design-stage decision-support screen rather than a bankable estimate of lifecycle sustainability gains.